Qualitative and quantitative analysis of scientific contributions in agribusiness - Rodríguez-Orozco, Nereida (2021)
The agribusiness is a major generator of employment and income worldwide and contributes to food security and nutrition. Therefore, the objective was to perform a qualitative and quantitative analysis of the scientific contributions in agribusiness. A bibliographic consultation was made in Scopus and "Agribusiness" was used as keyword. A textual analysis was performed on 407 scientific papers from 2020, through Nvivo 12 software using the following analysis codes: Mega trade agreements and institutional harmonization, farm-level technology pricing and contracts, market power related to the mega consolidation of companies, new agricultural technologies, emergence of agrocorporations, institutional land access rules, property rights regimes and their consequences, private enforcement of property rights, farmer class action studies and territorial reconversion. Two more codes emerged in the analysis process: Environmental impact and human health impact. Current scientific contributions in agribusiness are focused on new agricultural technologies (24%), environmental impact (17%) and local actions of farmers (14%). A qualitative improvement of the contributions is observed as more elements that support the complex processes agribusiness generates are increasingly incorporated. From focusing on economic and financial aspects, sustainability-oriented and social commitment domains are now considered. A modern and innovative concept defines agribusiness as economic activities with different forms or models of production, derived from or linked to agricultural products. It considers production-consumption processes and farmers are inserted in a differentiated way according to their economic rationality. These activities are not only focused on the generation of monetary value, but also on the social processes it produces, where multiple actors are involved.